ANALISIS PENERAPAN METODE PENYUSUTAN AKTIVA TETAP DAN DAMPAKNYA TERHADAP LABA PERUSAHAAN PADA PT KARTIKA SAMUDRA ADIJAYA DI TANJUNG REDEB (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2017)
The purpose of this study is to determine the method of depreciation of fixed assets that can provide the impact of the highest profit achievement on PT Kartika Samudra Adijaya in Tanjung Redeb. The analytical instrument used is the method of depreciation of fixed assets in accordance with PSAK No. 16 (revised 2011), namely: the straight line method, declining balance method and the sum of year's digits method.Based on the results of the analysis conducted on the application of several methods of depreciation of fixed assets in accordance with PSAK No. 16 (revised 2011), namely: the straight line method, declining balance method and the sum of year's digits method, the application of the declining balance method that can have the highest profit impact on PT Kartika Samudra Adijaya in Tanjung Redeb, this is evidenced from the calculation of net profit earned for the period of 2015 and the estimated net income in 2018.